INOVASI PEMBELAJARAN MATEMATIKA PADA MATA KULIAH KALKULUS LANJUTAN MELALUI LESSON STUDY - Ety Mukhlesi Yeni; Fachrurrazi Fachrurrazi; Yessy Kartika; Riandi Marisa; Maisura Maisura (Jurnal Pendidikan Almuslim, 2016)
Implementation of Lesson Study, Mathematics Education Program choose one course is Kalkulus Lanjutan. Selection of subjects was based that calculus is a course in basic math skills that must be mastered by the student. Innovation is happening in advanced calculus learning with learning that lesson study is implemented in the form of groups and members of this heterogeneous group, the teaching materials in the LKM (Lembar Kegiatan Mahasiswa) which can facilitate students understand the material and LKM contains the problems associated with the material to be studied, the presentation of the results of the LKM of students in front of the class like a teacher who was teaching and the training of students in speaking forum. Key words: Lesson Study, Kalkulus Lanjutan, Learning Mathematics